2021
DOI: 10.1186/s12888-021-03340-w
|View full text |Cite
|
Sign up to set email alerts
|

Investigating defensive functioning and alexithymia in substance use disorder patients

Abstract: Background Substance Use Disorder (SUD) causes a great deal of personal suffering for patients. Recent evidence highlights how defenses and emotion regulation may play a crucial part in the onset and development of this disorder. The aim of this study was to investigate potential differences in the defensive functioning between SUD patients and non-clinical controls. Secondly, we aimed at investigating the relationships between alexithymia and maladaptive/assimilation defenses. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 55 publications
0
6
1
Order By: Relevance
“…Moreover, omnipotence and sublimation are negative predictors of Studyholism, in contrast with the studies concerning SUD, which found that they have higher omnipotence and sublimation levels than a control group [ 38 , 39 ]. The results concerning lower sublimation and higher regression in Studyholics are in line with the studies concerning OCD [ 20 , 29 ] and, regarding lower sublimation only, with the studies about IAD [ 43 , 44 ].…”
Section: Discussioncontrasting
confidence: 66%
See 4 more Smart Citations
“…Moreover, omnipotence and sublimation are negative predictors of Studyholism, in contrast with the studies concerning SUD, which found that they have higher omnipotence and sublimation levels than a control group [ 38 , 39 ]. The results concerning lower sublimation and higher regression in Studyholics are in line with the studies concerning OCD [ 20 , 29 ] and, regarding lower sublimation only, with the studies about IAD [ 43 , 44 ].…”
Section: Discussioncontrasting
confidence: 66%
“…Additionally, through a critical analysis of all the defense mechanisms that proved to be statistically significant predictors of Studyholism, it has been shown that the OCD-related framework is adequate for the conceptualization of Studyholism, in line with previous studies (e.g., [ 7 , 12 , 15 ]). Moreover, we found that omnipotence and sublimation are negative predictors of Studyholism (in contrast with SUD, which is characterized by higher levels of omnipotence and sublimation [ 38 , 39 ]). Additionally, the results regarding lower sublimation and higher regression are in line with OCD studies [ 20 , 29 ] and, regarding lower sublimation only, with IAD studies [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations